Chapter 5 Empirical Evidence of Density‐Dependence in Populations of Large Herbivores - Bonenfant, Christophe; Gaillard, Jean‐Michel; Coulson, Tim; Festa‐Bianchet, Marco; Loison, Anne; Garel, Mathieu; Loe, Leif Egil; Blanchard, Pierrick; Pettorelli, Nathalie; Owen‐Smith, Norman; Du Toit, Johan; Duncan, Patrick (Advances in Ecological Research, 2009)
Density‐dependence is a key concept in population dynamics. Here, we review how body mass and demographic parameters vary with population density in large herbivores. The demographic parameters we consider are age‐ and sex‐specific reproduction, survival and dispersal. As population density increases, the body mass of large herbivores typically declines, affecting individual performance traits such as age of first reproduction and juvenile survival. We documented density‐dependent variations in reproductive rates for many species from the Arctic to subtropical zones, both with and without predation. At high density, a trade‐off between growth and reproduction delays the age of primiparity and often increases the costs of reproduction, decreasing both survival and future reproductive success of adult females. Density‐dependent preweaning juvenile survival occurs more often in polytocous than monotocous species, while the effects of density on post‐weaning juvenile survival are independent of litter size. Responses of adult survival to density are much less marked than for juvenile survival, and may be exaggerated by density‐dependent changes in age structure. The role of density‐dependent dispersal in population dynamics remains uncertain, because very few studies have examined it. For sexually dimorphic species, we found little support for higher sensitivity to increasing density in the life history traits of males compared to females, except for young age classes. It remains unclear whether males of dimorphic species are sensitive to male density, female density or a combination of both. Eberhardt's model predicting a sequential effect of density on demographic parameters (from juvenile survival to adult survival) was supported by 9 of 10 case studies. In addition, population density at birth can also lead to cohort effects, including a direct effect on juvenile survival and long‐term effects on average cohort performance as adults. Density effects typically interact with weather, increasing in strength in years of harsh weather. For some species, the synchronization between plant phenology and reproductive cycle is a key process in population dynamics. The timing of late gestation as a function of plant phenology determines whether density‐dependence influences juvenile survival or adult female reproduction. The detection of density‐dependence can be made difficult by nonlinear relationships with density, high sampling variability, lagged responses to density changes, changes in population age structure, and temporal variation in the main factors limiting population growth. The negative feedbacks of population size on individual performance, and hence on life history traits, are thus only expected in particular ecological contexts and are most often restricted to certain age‐specific demographic traits.